Acute Cardiorespiratory Responses to Different Exercise Modalities in Chronic Heart Failure Patients—A Pilot Study - Eleftherios Karatzanos; Panagiotis Ferentinos; Georgios Mitsiou; Stavros Dimopoulos; Argyrios Ntalianis; Serafeim Nanas (Journal of Cardiovascular Development and Disease, 2021)
The purpose of this study was to compare the acute cardiorespiratory responses and time spent above different %VO2peak intensities between three “iso-work” protocols: (a) a high intensity interval training protocol (HIIT), (b) a higher intensity continuous protocol (CON70) and (c) a lower intensity continuous protocol (CON50) in patients with chronic heart failure (CHF). Ten male CHF patients (aged 55.1 ± 16.2 years) performed in separate days a single session of a HIIT protocol consisted of 4 sets × 4 min cycling at 80% VO2peak with 3 min of recovery at 50% VO2peak, a CON70 protocol corresponding to 70% VO2peak and a CON50 protocol corresponding to 50% VO2peak. Cardiopulmonary data were collected by an online gas analysis system. The HIIT and CON70 elicited higher cardiorespiratory responses compared to CON50 with no differences between them (p > 0.05). In HIIT and CON70, patients exercised longer at >80% and >90% VO2peak. The completion rate was 100% for the three protocols. Not any adverse events were observed in either protocol. Both HIIT and CON70 elicited a stronger physiological stimulus and required shorter time than CON50. Both HIIT and CON70 also induced comparable hemodynamic responses and ventilatory demand.